Beyond symbolism: gender integration and institutional decline in the Cyprus national guard - Efthymiou, Stratis; Koliandri, Ioanna (My University, 2025)
Purpose – This purpose of this article is to critically examine the 2025 policy introducing voluntary female enlistment in the Cyprus National Guard, arguing that without systemic reform, it risks functioning as a symbolic gesture. Situating Cyprus within broader post-conflict and patriarchal military contexts, the article explores how gender inclusion can either challenge or reinforce entrenched militarised masculinities. It assesses whether this policy represents genuine institutional renewal or political theatre, and offers concrete policy pathways for sustainable integration. Design/methodology/approach – The article uses a qualitative, comparative case study approach. It draws on existing academic literature, policy documents and media discourse, as well as original scholarship on Cyprus’s military culture. International models of gender integration – including Norway, Finland, Sweden, Israel and the USA – are used as comparative frameworks to extract best practices and evaluate their relevance to Cyprus. The study is grounded in critical feminist and civil–military relations theory, with attention to post-conflict dynamics and the intersection of gender, nationalism and institutional legitimacy. Findings – The article finds that the 2025 policy is currently more symbolic than transformative. Deep-rooted cultural resistance, infrastructural deficiencies and the absence of accountability mechanisms continue to marginalise women in the National Guard. However, comparative models suggest that with targeted investment, leadership buy-in and cultural reframing, gender integration can serve as a strategic lever for institutional renewal. Without such systemic change, Cyprus risks reproducing gendered hierarchies under the guise of inclusion. Originality/value – This is the first academic analysis of gender integration in the Cyprus National Guard following the 2025 policy shift. It offers a rare contribution by situating Cyprus in global debates on militarised masculinity, post-conflict conscription and symbolic inclusion. The article provides actionable, evidence-based policy recommendations rooted in both Cypriot realities and international best practice. It will be of value to scholars in gender studies, military sociology and Eastern Mediterranean politics, as well as policymakers seeking to modernise defense institutions in post-conflict settings.
Keywords: Civil-military relations; Conscription and masculinity; Gender integration; Institutional decline; Militarised patriarchy; Post-conflict militaries